Rethinking Contemporary Church: Graph dynamics, Trinity interpretation, and hidden role of women as missional networkers - Victor Christianto (Sekolah Tinggi Teologi Satyabhakti, Malang, 2023)
“The times they are a-changin’,” as Bob Dylan wrote his famous song. We all agree with that remark, and it is so timely to speak how the church today needs to be in a-changin’. The question, though, is what kind of change the church is seeking to embrace? Is it in Christology, or liturgy, or Ecclesiology. Perhaps many theologians try to rethink their Christology positions, but few dare to admit there are a number of pressing questions in Ecclesiology old thoughts, as Jim Petersen wrote. The present article explores beyond mere daily questions such as Strauch explored (1986), but we ask questions related to persistent hierarchy which may be quite too rigid for embracing many new technologies, such as graph network. We extend further ideas that we discuss previously (Simon & Christianto, 2020). More than that since several years ago, there have been various discussions regarding how the post-Covid-19 situation will affect churches throughout the world. Although several books have been published on how church leaders should adapt to respond to these new circumstances, such reports seem rather reactive rather than looking in depth at the current ecclesiological challenges posed by Covid-19. Some churches have explored potential implications of the liquid church model as suggested by Prof. Pete Ward, inspired by sociologist Zygmunt Bauman. In this short article, the author invites readers to learn from small and simple churches, especially from a graph dynamics/network theory perspective. Therefore, in this initial report, let us discuss a graph interpretation of the God Trinity and its implications for the church graph model. We continue our previous article in the Amreta Journal, where we discussed a simple church model inspired by the interpretation of the John Gospel chapter 1; i.e. when Jesus called His first disciples to follow Him, cf. for example the free church model considered by Miroslav Volf from the Gospel of Matthew 17. Taking into account the earliest Christian communities that have grown in the past, especially in the era of the first centuries AD, as explained by Wim Dryer etc., let us put forward a proposition: that many of the serious obstacles faced by churches today can only be responded to properly by rethinking shared testimony and experience among networks or relationships of friends. In other words, rapid spreading of the Great Good News from God could only be achieved by introducing a new type of social analysis, called graph theory and network dynamics. We will discuss some implications in particular for the often hidden role of women in developing and propagating these ecclesiastical missional networks. To conclude, it is this writer’s hope that such an in-depth viewpoint will bring several insights into how to connect between ecclesiological praxis of the early Christian churches and the 21st century churches, especially in many regions of the world where the body of Christ is under severe persecution.